O preconceito nosso de cada dia: um estudo sobre as práticas discursivas no cotidiano - Souza, Isabela Augusta Andrade (2008)
Since prejudice theoretical concepts may have different forms, considering it a good approach to daily discourse practices is a complex proposal. Prejudice involves historical, social and cultural elements requiring a comprehensive understanding, and maybe to explain it we should take into consideration those issues such as separation, division and whatever leads to values and concepts that makes a person be disregarding and judgmental about other people. Our research aims at understanding what prejudice means to people and how they deal with it, no matter if it is a prejudicial act concerning other people or a feeling arising from some prejudicial circumstance. Mainly, the research focused on understanding prejudice as an active language permeating discourse practices and feeling production in the research interviewee daily life. We addressed our views to discourse practices based on the Discourse Psychology theoretical-methodological references that focus both scientific and common repertoires. Our hypothesis is that prejudice is present in people daily life through language, herein understood as action and reality versions, and thus dialogistical. Thus, prejudice would exist and does not depend on specific characteristics, such as social class, skin color, age, gender or any other element. Information collection was carried out through interviews with twenty-six people belonging to different social segments. The empirical material treatment was performed pursuant to the discourse practice analysis. The present research results suggest that people understand prejudice as a common sense concept where stigma, exclusion and discrimination are interchangeable. The results also showed that every person has experienced prejudice somehow in their lives no matter what their socioeconomic gender, race, or any other specific characteristics were like. Prejudice situations involved a variety of social meanings, most of them concerning depreciation and disregard. The interviewees showed different forms of noticing prejudice and almost always their feelings were connected to some kind of suffering. Thus, according to the results it is necessary to plan strategies and works based on continuous educational actions to foster the importance of solidarity and individual and social tolerance, through strategies directed to review the meaning of what is considered abnormal or does not meet society accepted standards in order to finally accomplish a greater serenity and harmony among the human beings